Isolation, characterization, and biological evaluation of endophytic fungi from Phragmites australis: experimental and computational insights - Eskander, Dina Mahfouz; El Awady, Mohamed E.; Ali, Mohamed; Fahim, Asmaa M.; A. Hamed, Ahmed; Sitohy, Basel (Frontiers in Molecular Biosciences, 2026)
Endophytic fungi are an uncharted source of bioactive metabolites with varied therapeutic characteristics. In this research, an endophytic Aspergillus sp. (HAG1) was collected from Phragmites australis and identified using morphological and molecular methods. The large-scale fermentation, chromatographic purification, and spectroscopic approaches (FT-IR, UV-Vis, 1H NMR, and ESI-MS) resulted in the identification of three metabolites: vaccenic acid (C1), pipericine (C2), and guaiacylglycerol (C3). Of these, C3 is reported here for the first time as an endophyte-derived metabolite from P. australis. All the metabolites exhibited significant antioxidant, antibacterial, antibiofilm, and anti-inflammatory activity. The activities of C3 were the most effective in DPPH and ABTS scavenging, COX-1/COX-2 inhibition, and suppression of biofilm for bacteria, although C3 was inactive against acetylcholinesterase activity. Molecular docking and molecular dynamics (MD) simulations underscored a favorable binding with a high binding conformation stability of C3 for antioxidant (1DGF), anti-inflammatory (3NLO), and antibiofilm (5TZ1) targets. In addition, density function theory (DFT) calculations delivered insights regarding electronic structure, explaining observed reactivity and hydrogen bonding ability. Moreover, ADMET predictions indicated that C3 has favorable solubility, metabolic stability, and low toxicity when compared to C1 and C2.